Racial Disparities in Police Citations: A Quantitative Analysis of Race and Police Citations - Phan, Hieu (My University, 2020)
Black people and African Americans continue to be negatively impacted by Anti-Black racism thorough multiple social, economic, and political metrics. People of color, particularly Black people, have been stopped-and-frisked, pulled over, issued citations, and even killed by the police at alarmingly higher rates than their white counterparts. This study utilizes citation data from the Los Angeles Police Department (LAPD) for the year 2016 to examine if there is a racial disparity in police citations. Examining daytime vs. nighttime citations, it allows me to test if a “veil of darkness” affects the chances of Black people being issued citations at night where their race becomes more ambiguous. As age increases the likelihood of nighttime citation decreases and males are less likely to get a nighttime citation compared to daytime. With an increase in rent prices, the chances of nighttime citations also increase. Asians were more likely to get nighttime citations compared to daytime citations. Individuals that fell into the “other” category of race were also more likely to get a nighttime citation. The results indicate that Black people are 17% less likely to get a nighttime citation. The post-hoc analysis revealed significant differences between the probability of nighttime citations for different races. Black people were the only statistically significant group of people that were less likely to get a citation at night.